Influence of silver electrochemically deposited onto zinc oxide seed nanoparticles on the photoelectrochemical performance of zinc oxide nanorod films. (21st May 2019) - Aranda, Alejandro; Landers, Richard; Carnelli, Patricio; Candal, Roberto; Alarcón, Hugo; Rodríguez, Juan
The present article examines the synthesis and characterization of zinc oxide nanorods grown on zinc oxide and silver nanoparticle seeds. Zinc oxide seeds were electrodeposited on a support of fluorine-doped tin oxide glass and heat-treated at 380°C. Silver nanoparticles were then deposited on this substrate, which was heat-treated at 160°C. Their presence was confirmed using ultraviolet–visible spectroscopy, by observing an absorption peak around 400 nm, corresponding to surface plasmon resonance. Growth of zinc oxide nanorods was achieved in a chemical bath at 90°C. The obtained films were analyzed by cyclic voltammetry, X-ray diffraction, and scanning electron microscopy. They consisted of zinc oxide with a Wurtzite-type crystal structure, arranged as nanorods of 50 nm. X-ray photoelectron spectroscopy exhibits peaks attributed to silver (0) and to the formation of silver oxide on the silver nanoparticle surface. In addition, two types of oxygen (O 1 s) were observed: oxygen from the crystalline network (O –2 ) and chemisorbed oxygen (–OH), for the seed and the nanorod films, respectively. The nanorods grown on zinc oxide seeds with silver deposits had a round shape and greater photoactivity than those grown without silver. This difference is attributed to the additional reflection that silver provides to the light reaching the film, thereby increasing the photogeneration from the charge carriers.